Influence of Economic Indices on the Solution to the Optimization Problem of the Age Structure of Power Plants Equipment - A. S. Apartsyn (Известия Иркутского государственного университета: Серия "Математика", 2018)
In this study we consider an integral model of the large electric power system development. The model accounts for division of the generating equipment into certain age groups. Each of these groups is characterized by some efficiency coefficient. We consider a vector model with subdivision the equipment of the stations by fuel types. The model includes the balance integral Volterra equation of the first kind with variable upper and lower limits and functional equations, describing the structure of the electricity consumption of different types of power plants.